A Dual‐Crosslinked Strategy to Construct Physical Hydrogels with High Strength, Toughness, Good Mechanical Recoverability, and Shape‐Memory Ability. Issue 2 (4th December 2017) - Qin, Zhihui; Niu, Rui; Tang, Chenjue; Xia, Jun; Ji, Feng; Dong, Dianyu; Zhang, Haitao; Zhang, Shuo; Li, Junjie; Yao, Fanglian
Abstract: A novel type of physical hydrogel based on dual‐crosslinked strategy is successfully synthesized by micellar copolymerization of stearyl methacrylate, acrylamide, and acrylic acid, and subsequent introduction of Fe 3+ . Strong hydrophobic associations among poly(stearyl methacrylate) blocks form the first crosslinking point and ionic coordination bonds between carboxyl groups and Fe 3+ serve as the second crosslinking point. The mechanical properties of the hydrogel can be tuned in a wide range by controlling the densities of two crosslinks. The optimal hydrogel shows excellent mechanical properties (tensile strength of ≈6.8 MPa, elastic modulus of ≈8.0 MPa, elongation of ≈1000%, toughness of 53 MJ m −3 ) and good self‐recovery property. Furthermore, owing to stimuli responsiveness of physical interaction, this hydrogel also shows a triple shape memory effect. The combination of two different physical interactions in a single network provides a general strategy for designing of high‐strength hydrogels with functionalities. Abstract : A physical hydrogel with excellent mechanical performances and shape‐memory effect is successfully synthesized via two crosslinkings of strong hydrophobic associations and ionic coordination bonds. The reinforcement mechanism, energy dissipation, and mechanical recoverability processes of the hydrogel are systematically investigated. Furthermore, the responsiveness of physical interactions endows the hydrogel with a triple shape memory effect.